Solid Particle Erosion Occurrence, Prediction and Control - Kleis, Ilmar; Kulu, Priit (Springer London : Imprint: Springer, 2008)
Solid Particle Erosion: Occurrence, Prediction and Control collects together the work of more than 130 industrially-supported research projects conducted over 50 years on erosion at the Tallinn Technical University, Estonia (now the Tallinn University of Technology), much of which is previously unpublished in English. Providing a systematic review of erosion caused by solid particles, Solid Particle Erosion: Occurrence, Prediction and Control also introduces a new energetic theory of erosion by plastic contact, based on theories of plastic contact and brittle behaviour models for composite structures. Materials engineers, researchers and students will find Solid Particle Erosion: Occurrence, Prediction and Control a valuable resource on erosion wear mechanisms, with extensive data on erosive wear resistance of conventional steels, powder materials and coatings, criteria for erosive wear-resistant material and coating selection, and case studies on improving the erosion resistance of industrial equipment.